Comparison Study of the Effect of Product Quality, Halal Label, Price, and Brand Collaboration on Purchase Intention for Somethinc, Scarlet, and Ms. Glow Products - Iqbal, Muhammad; Raorenza, Aprilia Putri (IAIN Manado, 2024)
The number of skincare companies have expanded dramatically and is predicted to grow year after year. It is critical to monitor the growth and trends in skincare companies as they expand, so this study investigates the impact of product quality, halal labels, price, and brand collaboration on skincare purchase interest by comparing the top three brands in sales, Something, Scarlett, and Ms. Glow. This study intends to find and analyze differences in the influence of these elements on purchase interest by conducting a comparative analysis of the three leading skincare brands in recent years. This study includes 100 respondents aged 17 to 35 years old and employs a quantitative approach with data collection procedures via questionnaires. Because this is a comparison study, the Manova test was employed to analyze the data. The study's findings indicate that product quality and collaborative variables have a substantial impact on the buying interest of Somethinc, Scarlett, and Ms.Glow. However, there was no significant difference in the variables of halal label and price on purchasing interest between these two brands. This does not imply that the Halal variable is unimportant, but it is not the sole variable examined in this study. Three other criteria are regarded as equally significant in the skincare industry. Furthermore, before checking product quality, buyers are already convinced that, in general, items in Indonesia, which has a Muslim majority, are halal certified and safe to consume. The price hypothesis, like the halal variable, is rejected because the current generation is more choosy in its shopping habits and is not easily influenced by affordable prices.